Does greater discretion improve the performance in the execution of public works? Evidence from the reform of discretionary thresholds in Italy - Massimo Finocchiaro Castro; Calogero Guccio (ZBW - Leibniz Information Centre for Economics, 2021)
In this work, adopting a semi-parametric approach and a quasi-experiment setting, we empirically assess the effects of a reform of public procurement regulation in Italy, approved in 2011, that increased the discretion of bureaucrats in selecting the procurer. To this end, employing a large dataset of public works managed by Italian municipalities in the period 2009-2013, we first estimate contract execution performance; then, we test the impact of the reform on the efficiency of public works execution in an institutional context characterized by large differences in social capital and trust in institutions. The results provide evidence that the reform exerted a positive, albeit small, effect on public works execution performance. However, the beneficial role exerted by increased discretion is positive and significant only in those areas where social capital and trust in institutions have reached higher levels. These results seem to suggest that more discretion leads to greater efficiency but also to greater corruption risks suggesting that increased discretion must be balanced by strengthened ex-post controls, particularly in high-risk areas.
Keywords: D24; D73; H57; P16; 330; Bureaucratic discretion; Social capital; Corruption; Public works contracts; Efficiency; Non-parametric frontier; Semi-parametric methods